Evaluation of the accuracy of cone beam computed tomography (CBCT) in the detection of peri-implant fenestration - Atefeh Gholampour; Melika Mollaei; Hodis Ehsani; Fatemeh Ghobadi; Abolfazl Hosseinnataj; Mehdi Yazdani (BMC, 2024)
Abstract Background Accurate assessment of the bone supporting the implant is crucial. Early detection of bone defects around the implant can prevent the loss of bone support that ultimately leads to the loss of the implant. Therefore, the purpose of this study is to check the accuracy of CBCT in detecting peri-implant fenestrations around the implant. Materials & methods In this laboratory study, healthy beef ribs were used. The ribs were divided into three groups of 12 (control group, 1-2 mm fenestration group, and 2-3 mm fenestration group). The blocks were cut to a length of 20 mm and 36 osteotomies with dimensions of 4 × 12 mm were made by the periodontist in order to place the implant in these bone blocks. Then the titanium implant was placed in the holes and the initial scan was performed with CBCT. In the second group, fenestration-like lesions were created on the same buccal side at a distance of 10 mm from the crest with a diameter of 1-2 mm and in the third group with a diameter of 2-3 mm, and the CBCT scan was performed again with the same parameters. Two radiologists evaluated the images twice for the presence and absence of fenestration. Results There was no statistically significant difference between direct measurements and CBCT in the fenestration group of 1-2 mm (p < 0.05), but there was a significant difference between direct measurements and CBCT in the fenestration group of 2-3 mm and underestimation was observed in CBCT measurements. Conclusion The findings of this study showed that CBCT radiography has a higher accuracy in measuring the fenestration around the implant with a smaller diameter and has an acceptable diagnostic value in detecting bone loss around the implant.